1988
DOI: 10.1007/bf01912735
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the thermal stability of the perfluorinated cation-exchange membrane Nafion-417

Abstract: The thermal stability of the perfluorinated cationexchange membrane Nation-417 was determined by means of simultaneous TG-DTA. The individual decomposition stages were studied via IR spectroscopy and ion-exchange capacity determinations. Nafion-417 is thermally stable up to 280 ~ Above this temperature, sulfonic groups present in the membrane are split off (Tmax ----345 ~ In the temperature range 420-590 ~ oxidative destruction of the perfluorinated matrix occurs, which is accompanied by practically total weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(40 citation statements)
references
References 7 publications
4
35
0
1
Order By: Relevance
“…It was found that the sulfonic acid group in Nafion was stable at temperatures up to 280°C in air. 223,224 This also seems to apply to most of the sulfonated hydrocarbons. Degradation temperatures of 240-330 and 250°C, respectively, were reported for SPEEK 43,182,197,226,225 and sulfonated polysulfone (SPSF), 196,215 though Trotta et al 198 reported a decomposition temperature of the SO 3 H group at about 400°C for the sulfonated PEEK-WC.…”
Section: Stability and Lifetime Under Fuel Cell Conditionsmentioning
confidence: 94%
See 1 more Smart Citation
“…It was found that the sulfonic acid group in Nafion was stable at temperatures up to 280°C in air. 223,224 This also seems to apply to most of the sulfonated hydrocarbons. Degradation temperatures of 240-330 and 250°C, respectively, were reported for SPEEK 43,182,197,226,225 and sulfonated polysulfone (SPSF), 196,215 though Trotta et al 198 reported a decomposition temperature of the SO 3 H group at about 400°C for the sulfonated PEEK-WC.…”
Section: Stability and Lifetime Under Fuel Cell Conditionsmentioning
confidence: 94%
“…33 The desulfonation of PFSA membranes has been widely studied [222][223][224] by means of TGA, DTA, FT-IR, and TGA-MS measurements. It was found that the sulfonic acid group in Nafion was stable at temperatures up to 280°C in air.…”
Section: Stability and Lifetime Under Fuel Cell Conditionsmentioning
confidence: 99%
“…The line may be divided into two regions: in one, between 298 and 423 K, the sample loses 14.3 wt.-%, which can be assigned to water loss; in the other, between 423 and 573 K, it loses 1.5 wt.-%, and this loss can be assigned to the water release and a small amount of sulfur dioxide and carbon dioxide, in agree- ment with ref. [14][15][16] , i. e. to the beginning of the polymer decomposition. Fig.…”
Section: Differential Scanning Calorimetry (Dsc) and Thermogravimetrimentioning
confidence: 99%
“…Yeager and others have investigated, using infrared spectroscopy, [2] the modifications in air of Nafion-1100 coated onto a platinum film, heating it at temperatures from 295 -573 K. After 15 min at 573 K the polymer loses its sulfonic acid group. Thermogravimetric analysis (TGA), differential thermal analysis (DSC) and infrared spectroscopy [14] led Surowiec and others to the conclusion that Nafion loses only water below 553 K, while above 553 K it also loses the sulfonic acid groups. Nafion-H has been studied by thermogravimetric analysis and Fourier transform infrared spectroscopy (FTIR) [15] to identify the evolved gases: between 308 and 553 K Nafion lost about 5 wt.-% and produced water as well as small amounts of sulfur dioxide and carbon dioxide.…”
Section: Membranes From Nafion Dispersionsmentioning
confidence: 99%
“…No entanto, Samms et al [42] realizaram estudos sobre decomposição térmica do Nafion ® , na faixa de 0 a 600 °C, utilizando técnicas de Termogravimetria (TGA) e Espectrometria de massas (MS) acopladas. Com base nos valores de razão m/z, concluíram que na região entre 75 e 225 °C havia apenas perda de água (m/z =18), conforme também relatado por outros pesquisadores [43][44][45] . Na região de 275 a 400 °C, obteve-se sinais de m/z = 48 e 64, que os autores atribuíram a liberação de SO 2 .…”
Section: Térmicaunclassified